Magnitude of Out of Pocket Health Expenditures and Associated Factors among Civil Servants - Mekuanenet Geremew; Molla Gedefaw; Girmay Tsegay; Getachew Mullu Kassa (International Journal of Public Health Science (IJPHS), 2015)
In Ethiopia, as other developing countries, public health care is provided at nominally low prices and free to those that does not afford to pay. But the health care consumer population is still to make considerable amount of out-of-pocket health expenditure for various reasons. A cross sectional quantitative study from January to May 2013 was done. Study population was civil servants in Debre Markos town. A total of 467 study participants were selected by using simple random sampling method. Data were collected by trained high school graduates and then the collected data were entered into a computer by using Epi-Data version 3.1 and analysis was performed by using SPSS version 16 for windows. Possible associations between out of pocket health expenditure and its predictors were analyzed by using both bivariate and multivariate analysis. The mean age of the study participants were 41 years. Majorities were between 25 and 44 years of age, 258 (55.2%). The level of education among the study participants indicated that most 380 (81.4%) were graduates of higher education (HE) and majority were Orthodox Christian which accounted 446 (95.5%) followed by Muslims 13 (2.8%). To put it briefly, the study identified that the median of out of pocket health care expenditure accounted 8.26% of total household income. Health status of the household (with or without chronic illness), debt on any of the household, house on construction owned by any household member, educational fee for at least one member of the household and predominantly used health institution were the associated factors that have significant impact on household out of pocket health expenditure. There is economic burden as a result of health care at household level.   Based on the results, the recommendation was introducing social health insurance for all civil servant employees in the study area.